Sistem Informasi Penyewaan Lapangan Badminton Berbasis Web - Dzikra Azzahra (STIKes Ibnu Sina Ajibarang, 2024)
Badminton is a sport that is popular with young people of almost all ages, however, some places do not have websites with the aim of making the rental process easier both from far and near. The creation of this badminton web data system can be implemented using Visual Studio Code, the PH programming language, MySQL database as information storage. The creation of this application uses the waterfall methodology.